Authoritative parenting style positively correlates with increased adherence to COVID-19 health and safety guidelines by college students - Spivey, Adrienne J.; Bodily, Jessica Stagner (Frontiers in Psychology, 2023)
During the COVID-19 pandemic, there has been inconsistency in choice behavior across people with regards to compliance with health and safety guidelines suggested by the CDC. The current study aimed to identify a possible correlation between parenting style experienced during childhood and opinions/actions regarding CDC COVID-19 health guidance. College students were given a self-report survey aimed to measure childhood experience, parent–child relationship, and COVID-19 pandemic behavior. Participants that identified with Authoritarian parenting scored higher on the COVID Behavior measure, indicating a higher degree of compliance compared to participants that identified with Authoritative parenting. Additionally, gender and race category differences on the COVID Behavior measure were observed. Specifically, African American/Black participants scored higher than White or Other race identifying participants on the COVID Behavior measure. Lastly, females identifying as African American/Black or Other race scored higher than males identifying as African American/Black or Other race on the COVID Behavior measure. These findings begin to illuminate some of the variables that might play a role in choice behavior with regard to compliance to health guidelines. Further investigation into these variables could inform us about what plays a role in choice behavior and how better to integrate this knowledge when messaging the public about health guidelines.